The Marxist Approach to Nature: The Case of Wolves in the Soviet Union - Jefanovas, Aivaras; Davidavičius, Mantas-Antanas (Politologija, 2025)
This article analyzes the orthodox Marxist theory of nature as a philosophy of nature, based primarily on the later works of Karl Marx and the works of Friedrich Engels, as well as its role as a Soviet State ideology of mastering nature. We argue that Soviet Marxists viewed nature as a product of human labor. Labor, in turn, was considered a continuation of the natural order and the fulfillment of nature’s full potential. At the same time, labor led to a “struggle with nature”. This motif of battle against nature appears almost universally throughout Soviet ideological texts. To analyze how the ideological interpretation of nature by Soviet Marxists was implemented in practice, we examine the wolf extermination campaigns carried out in the Soviet Autonomous Soviet Socialist Republic of Yakutia and the Soviet Socialist Republic of Lithuania and consider them as part of the Soviet Marxists’ ideological approach to the transformation, control, and subjugation of nature.